Answer:
- x-axis: (x, y) ⇒ (x, -y)
- y-axis: (x, y) ⇒ (-x, y)
- y = x: (x, y) ⇒ (y, x)
- y = -x: (x, y) ⇒ (-y, -x)
Explanation:
The attached diagram may be helpful. In the diagram, each reflected point is connected to the original by a line segment perpendicular to the line of reflection.
Reflection across the x-axis
(3, 1) ⇒ (3, -1)
(x, y) ⇒ (x, -y)
Reflection across the y-axis
(3, 1) ⇒ (-3, 1)
(x, y) ⇒ (-x, y)
Reflection across y = x
(3, 1) ⇒ (1, 3)
(x, y) ⇒ (y, x)
Reflection across y = -x
(3, 1) ⇒ (-1, -3)
(x, y) ⇒ (-y, -x)